2019
DOI: 10.1111/ejn.14542
|View full text |Cite
|
Sign up to set email alerts
|

A sinister subject: Quantifying handedness‐based recruitment biases in current neuroimaging research

Abstract: Approximately ten per cent of humans are left‐handed or ambidextrous (adextral). It has been suggested that, despite their sizable representation at the whole‐population level, this demographic is largely avoided by researchers within the neuroimaging community. To date, however, no formal effort has been made to quantify the extent to which adextrals are excluded from neuroimaging‐based research. Here, we aimed to address this question in a review of over 1,000 recent articles published in high‐impact, peer‐r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 68 publications
(88 reference statements)
0
26
0
Order By: Relevance
“…For articles that reported handedness of subjects, 89.1% of them recruited only right‐handed subjects. However, it should also be noted that 37.3% of the analyzed articles did not report subject handedness – this ratio is considerably much larger than the 9.2% of sensorimotor‐related articles as reported by Bailey et al ().…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…For articles that reported handedness of subjects, 89.1% of them recruited only right‐handed subjects. However, it should also be noted that 37.3% of the analyzed articles did not report subject handedness – this ratio is considerably much larger than the 9.2% of sensorimotor‐related articles as reported by Bailey et al ().…”
Section: Discussionmentioning
confidence: 61%
“…A recent survey, based on approximately 1,000 articles, reported that only 3–4% of over 30,000 research subjects recruited for neuroimaging experiments were left‐handed or ambidextrous, compared to their prevalence of 10–13% in the general population (Bailey et al, ). In this dataset, we also found that the subjects were mainly right‐handed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a VBM study of 465 healthy adult brains they found minimal effect of handedness on symmetry [68]. This is supported by a review article that assessed the effect of handedness on the findings from numerous different neuroimaging techniques [69]. Therefore, handedness matching may not be a necessary consideration for future imaging studies.…”
Section: Discussionmentioning
confidence: 88%
“…The use of some version of the EHI is now ubiquitous for subject screening and 4 participant exclusion in neuroimaging studies, often to the omission of other methods of 5 handedness assessment (Fazio & Cantor, 2015). The exclusion of left-handed subjects (defined as 6 those with either low or negative EHI scores) in neuroimaging contexts-specifically those 7 probing language or other lateralized functions-is largely justified, considering the effect of 8 subject lateralization on variance in activation patterns and resultant issues with common statistical 9 approaches (see Bailey, McMillan, & Newman, 2019;Króliczak, Gonzalez, & Carey, 2019;10 Vingerhoets, 2014). Still, some have argued that this is a misguided approach, claiming that the 11 inclusion of left-handers and other atypically lateralized individuals can tell us more, not less, 12 about cortical function, and especially, asymmetry (Willems et al, 2014).…”
Section: Introductionmentioning
confidence: 99%